(untitled) (Indian Journal of Animal Production and Management, 2024)
This comprehensive review explores maternal behaviour in cattle, encompassing various aspects such as isolation before calving, licking behaviour, vocalizations, suckling, cross-fostering, and weaning. The initiation of maternal behavior involves isolation from the herd, selection of nesting sites, and heightened activity before calving. Licking behaviour, crucial for calf stimulation, exhibits temporal patterns with peak intensity after birth. Challenges in maternal bonding development include the influence of maternal experience, housing systems, and cross-licking, affecting calf rejection. Suckling, a fundamental behaviour, has distinct patterns in dairy cows. Cross-fostering and weaning practices pose challenges, with insights into fostering success and behavioral responses to calf separation. Overall, understanding maternal behaviour contributes to improved cattle management and welfare, emphasizing the need for proving opportunities and avenues for the expression of maternal behaviour in modern intensive production systems.